Revisiting the Predictive Factors for Intra-Operative Complications of Rigid Ureteroscopy: A 15-Year Experience - Tanriverdi, Orhan; Silay, Mesrur Selcuk; Kadihasanoglu, Mustafa; Aydin, Mustafa; Kendirci, Muammer; Miroglu, Cengiz (Urology Journal, 2012)
PURPOSE: To revise the predictive factors for intra-operative complications of rigid ureteroscopy in the treatment of ureteral calculi. MATERIALS AND METHODS: During a 15-year period (1993 to 2008), a total of 1496 consecutive patients who had undergone 1660 ureteroscopy procedures were retrospectively reviewed. After exclusion of the cases for diagnostic purposes, diseases other than ureteral calculi, and repeated ureteroscopy procedures, 1189 patients were left as the study population. Those patients were then divided into two groups based on the presence of the complications: complication–positive (group 1, n = 57) and complication–negative (group 2, n = 1132). Both groups were statistically compared regarding patients’ age and gender, stone surface area, lateralization and localization of the stone, impaction of the stone, type of the ureteroscope, necessity of ureteral orifice dilation, and use of a catheter during and after the procedure. Furthermore, the effect of leaving the fragmented stones in situ small enough to pass spontaneously (break’n’leave) on occurring of the complications has been investigated. RESULTS: The complication rate was recorded as 4.7%. Success rate after a single intervention was 86.3%, whereas increased to 94.1% after ancillary procedures. Stone surface area, lateralization, and type of lithotripter used were comparable between the groups, but impacted stones and the stones located at the upper ureters were associated with significantly increased complication rates. Furthermore, significantly less complication has been observed in cases where we performed break’n’leave. Furthermore, multivariate analysis revealed that stone impaction and failure to adhere to the “break’n’leave” principle were the independent predictors of occurring of the complications. CONCLUSION: Ureteroscopy is safe and effective in the treatment of ureteral calculi. Careful attention for the patients having a potential for occurrence of the complications and selection of the techniques are of importance for reducing untoward events.